Getting into Court When the Data Has Gotten Out: A Two-Part Framework - Alyssa L. Aubuchon (Washington University Law Review, 2021)
Part I of this Note will examine the history of the Fair Credit Reporting Act, the basics of Article III standing, and its applications to intangible harms and data-privacy related injuries. Part II of this Note will then propose two potential solutions to the standing issues that arise when consumers are granted a right to sue credit reporting agencies for data breach harms. First, this Note will argue that, as the law currently stands, the Supreme Court should recognize that data breaches cause particularized and concrete harms sufficient to satisfy the injury-in-fact requirement of Article III. Finally, this Note will argue that because of judicial inconsistencies in applying the standing doctrine, state legislatures should adopt a uniform law, allowing Article III standing issues to be avoided altogether.
Keywords: Data breaches; Fair Credit Reporting Act; Article III standing; Privacy harm; Injury-in-fact